2011
DOI: 10.1179/147842208x386340
|View full text |Cite
|
Sign up to set email alerts
|

Stress corrosion cracking of aluminium alloy 7075(w) under tensile and compressive loading

Abstract: The effect of compressive loading on stress corrosion cracking of aluminium alloy 7075(W) was studied using specimens containing simulated fastener holes and the results were compared with the behaviour of double cantilever beam specimens with tensile loading. Crack lengths were measured with an eddy current bore probe and confirmed by optical metallography. Intergranular stress corrosion was observed in both tensile and compressive loading. Cracks initiated readily in 3?5%NaCl solution with tensile loading an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Residual stress measurements (using XRD) showed that this transition corresponds to the transition from compressive to tensile stresses in the austenite phase (the ferrite phase being under compression in both domains). The deleterious influence of tensile stresses on the electrochemical behavior and corrosion resistance was also reported for the following metallic alloys, namely 316L stainless steel [16], ferritic steel [31], 304L stainless steel [32,33], high-strength galvanized steel [34], carbon steel [35], X80 steel [36], aluminum alloys 7075 [37] and 7010 [38], Fe-based amorphous coatings [39], and 316L stainless steel [40]. Table 2.2 gives some examples of tensile residual stresses generated in metallic alloys using various techniques.…”
Section: Influence Of Tensile Stresses In the Elastic Domainmentioning
confidence: 90%
“…Residual stress measurements (using XRD) showed that this transition corresponds to the transition from compressive to tensile stresses in the austenite phase (the ferrite phase being under compression in both domains). The deleterious influence of tensile stresses on the electrochemical behavior and corrosion resistance was also reported for the following metallic alloys, namely 316L stainless steel [16], ferritic steel [31], 304L stainless steel [32,33], high-strength galvanized steel [34], carbon steel [35], X80 steel [36], aluminum alloys 7075 [37] and 7010 [38], Fe-based amorphous coatings [39], and 316L stainless steel [40]. Table 2.2 gives some examples of tensile residual stresses generated in metallic alloys using various techniques.…”
Section: Influence Of Tensile Stresses In the Elastic Domainmentioning
confidence: 90%
“…The aluminium alloys of the 1xxx series are widely used in many commercial applications and therefore studies of these alloys are important in clarifying the effects of the constituents of high strength alloys on SCC behaviour (Trueba and Trasatti, 2009;Braun, 1995;Zhu and Van Ooij, 2003;Dolic et al, 2011;Dollah and Robinson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The stress corrosion cracking (SCC) behaviour of aluminium alloys in aqueous environments such marine waters is of great importance for industrial applications. The aluminium alloys of the 1xxx series are widely used in many commercial applications and therefore studies of these alloys are important in clarifying the effects of the constituents of high strength alloys on SCC behaviour (Trueba and Trasatti, 2009; Braun, 1995; Zhu and Van Ooij, 2003; Dolic et al , 2011; Dollah and Robinson, 2011).…”
Section: Introductionmentioning
confidence: 99%